2006
DOI: 10.1111/j.1468-8123.2006.00139.x
|View full text |Cite
|
Sign up to set email alerts
|

Iron mineralization and dolomitization in the Paran Fault zone, Israel: implications for low‐temperature basinal fluid processes near the Dead Sea Transform

Abstract: Petrography, Eh-pH calculations and the stable isotope composition of oxygen are used to interpret geochemical processes that occurred during iron oxide mineralization and dolomitization along the Menuha Ridge segment of the Paran Fault, southern Israel, adjacent to the Dead Sea Transform (DST). Iron mineralization is strongly localized in the fault zone as ferruginous lenses, whereas Fe dolomitization spreads laterally into the CenomanianTuronian carbonate host rock as stratabound beds. The average oxygen iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 36 publications
5
47
0
Order By: Relevance
“…However, oxidation of ferroan dolomite is not necessarily accompanied by calcitization of dolomite. Subaerial exposure can convert ferroan dolomite into iron oxide grains or aggregates by oxidation and pseudomorphic replacement (Zeidan and Basyuni 1998;Grosz et al 2006). The fact that goethite is formed rather than hematite (no relicts or pseudomorphs of hematite are present) is also consistent with conditions of low temperature and pH found at surface conditions, high water activity [H 2 O], and low iron supply rates (Yapp 2001).…”
Section: Composite Textures Originating From Both Dolomitization and supporting
confidence: 56%
“…However, oxidation of ferroan dolomite is not necessarily accompanied by calcitization of dolomite. Subaerial exposure can convert ferroan dolomite into iron oxide grains or aggregates by oxidation and pseudomorphic replacement (Zeidan and Basyuni 1998;Grosz et al 2006). The fact that goethite is formed rather than hematite (no relicts or pseudomorphs of hematite are present) is also consistent with conditions of low temperature and pH found at surface conditions, high water activity [H 2 O], and low iron supply rates (Yapp 2001).…”
Section: Composite Textures Originating From Both Dolomitization and supporting
confidence: 56%
“…Regional-scale faulting (the Negev Shear zone) related to the Dead Sea Transform, which initiated in the Miocene, facilitated the rise of the over pressured solutions along fault lines and allowed the dolomitization and mineralization of the overlying carbonate rocks (Bartov, 1974;Ilani et al, 1988). The sedimentary basinal setting of the mineralization was confirmed by oxygen isotope studies of ferruginous lenses, which showed that they formed at temperatures of 50 ± 10°C (Grosz et al, 2006).…”
Section: Introductionmentioning
confidence: 92%
“…The dolomite is characterized by a deep-red colouration, which frequently stands out against the pale-coloured limestone; consequently beds can be traced easily along strike (Grosz et al, 2006). Dolomitization at Zvar Habaqbuq (ZH) in the west of the area occurs in the Ora and Gerofit formations exposed on the south side of the Paran fault (Figs.…”
Section: Field Setting and Petrography Of Dolomitesmentioning
confidence: 99%
See 2 more Smart Citations